The evolution of security intelligence. Issue 3 (March 2015) - Cates, Sol
Abstract : Threat landscapes have drastically changed from just a few years ago with targeted attacks now common occurrences. Hackers are actively seeking to steal credit card data, personally identifiable information (PII), critical intellectual property (IP), and other legally protected information to retail to the highest bidder. As a result, many of today's businesses have found themselves on the back foot. Threat landscapes have drastically changed from just a few years ago, with targeted attacks now common occurrences. As a result, many of today's businesses have found themselves on the back foot. Security intelligence offerings combining both Security Intelligence and Event Management (SIEM) solutions and 'big data for security' implementations are key tools for offsetting threats that result from both increased hacking, and vulnerabilities resulting from insider compromises, explains Sol Cates of Vormetric.